2018
DOI: 10.1007/s10980-018-0654-8
|View full text |Cite
|
Sign up to set email alerts
|

Landscape composition mediates movement and habitat selection in bobcats (Lynx rufus): implications for conservation planning

Abstract: Context The analysis of individual movement choices can be used to better understand populationlevel resource selection and inform management. Objectives We investigated movements and habitat selection of 13 bobcats in Vermont, USA, under the assumption individuals makes choices based upon their current location. Results were used to identify ''movement-defined'' corridors.Methods We used GPS-collars and GIS to estimate bobcat movement paths, and extracted statistics on land cover proportions, topography, fine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…While bobcats generally occur more often in natural areas (Ordeñana et al, 2010), some telemetry studies show that bobcats will cross and sometimes utilize urban development separating habitat fragments, particularly at night (Riley et al, 2003;Tigas et al, 2002). Our results indicate that despite these movements, urban development does constrain gene flow even within areas that consist largely of natural habitat (e.g., (Abouelezz et al, 2018). The ability to identify generalized effects such as that of urbanization here is a key advantage afforded by replication in landscape genetics generally (Balbi et al, 2018;Robertson et al, 2018;Row et al, 2018).…”
Section: Implications For Functional Connectivitymentioning
confidence: 71%
See 2 more Smart Citations
“…While bobcats generally occur more often in natural areas (Ordeñana et al, 2010), some telemetry studies show that bobcats will cross and sometimes utilize urban development separating habitat fragments, particularly at night (Riley et al, 2003;Tigas et al, 2002). Our results indicate that despite these movements, urban development does constrain gene flow even within areas that consist largely of natural habitat (e.g., (Abouelezz et al, 2018). The ability to identify generalized effects such as that of urbanization here is a key advantage afforded by replication in landscape genetics generally (Balbi et al, 2018;Robertson et al, 2018;Row et al, 2018).…”
Section: Implications For Functional Connectivitymentioning
confidence: 71%
“…This pattern is obvious in coastal southern California, where the largest tracts of urban development are situated in the flat regions of the Los Angeles Basin, coastal Orange County, and the coastal plain of San Diego County, and bobcat habitat generally is restricted to the surrounding Santa Monica Mountains, San Joaquin Hills, and eastern Peninsular Ranges. However, bobcats have been shown to also favour topographically rough terrain in less urbanized landscapes (Abouelezz et al, ). The ability to identify generalized effects such as that of urbanization here is a key advantage afforded by replication in landscape genetics generally (Balbi et al, ; Robertson et al, ; Row et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Male movement rates are often greater than female movement rates [14,15,16,17], but most information on bobcat movement rates comes from studies that employed VHF telemetry, which often had coarse sampling intervals and poor locational accuracy. More recent studies using GPS telemetry have found varied results [18,19,20], and there is currently a scarcity of published bobcat movement rates from GPS studies. As obligate carnivores with a stalk and ambush hunting mode, [11], prey availability is a key driver of bobcat space use and resource selection.…”
Section: Introductionmentioning
confidence: 99%
“…Bobcats (Lynx rufus) are a solitary, midsized felid with a territorial social organization and polygynous breeding strategy [9]. Male bobcats exhibit larger home ranges than those of females [10], and may exhibit greater movement rates than females [11][12][13][14]. As obligate carnivores, bobcats require sufficient prey to meet energetic demands.…”
Section: Introductionmentioning
confidence: 99%